Implementasi Program Pendidikan Parenting Pada Masa Pandemi Covid-19 - Kholilatul Umiyah; Tomas Iriyanto; Wuri Astuti (Jurnal PAUD: Kajian Teori dan Praktik Pendidikan Anak Usia Dini, 2023)
Learning from home during the Covid-19 pandemic, many parents had difficulty accompanying their children in studying. It is not easy for schools to gather and provide guidance to parents because it creates crowds. Various collaborations with parents are sought so that children continue to learn optimally. During the Covid-19 pandemic, Aisyiyah Bustanul Athfal 26 Malang Kindergarten implemented an online parenting education program. Research during the Covid-19 pandemic at Kindergarten ABA 26 Malang aims to describe (a) a general description of the implementation of activities, (b) supporting factors for activities, (c) factors inhibiting activities, (d) results of implementing activities for parents and children. This research uses a descriptive qualitative research design. Data collection methods: observation, interviews, and documentation. Informants for this research: school principals, teachers and parents. The research results show that during the Covid-19 pandemic, the parenting education program at Kindergarten ABA 26 Malang was: providing a platform for offline and online parent consultations, parenting education seminars via the zoom meeting application and YouTube live streaming with expert speakers, involving parents at home at the peak theme. The stages of the parenting education program with resource persons are: preparation, implementation and evaluation stages.Belajar Dari Rumah (BDR) pada masa pandemi covid-19 yang terjadi, banyak orang tua kesulitan mendampingi anak belajar. Sekolah tidak mudah mengumpulkan dan memberi pengarahan orang tua sebab menimbulkan kerumunan. Berbagai kerjasama dengan orang tua diupayakan agar anak tetap belajar optimal. Pada masa pandemi covid-19 TK Aisyiyah Bustanul Athfal 26 Malang melaksanakan program pendidikan parenting secara daring. Penelitian pada masa pandemi covid-19 di TK ABA 26 Malang bertujuan mendeskripsikan (a) gambaran umum pelaksanaan kegiatan, (b) faktor pendukung kegiatan, (c) faktor penghambat kegiatan, (d) hasil pelaksanaan kegiatan bagi orang tua terhadap anak. Penelitian ini menggunakan desain penelitian kualitatif deskriptif. Metode pengumpul datanya: observasi, wawancara, dan dokumentasi. Informan penelitian ini: kepala sekolah, guru, dan orang tua. Hasil penelitian bahwa pada masa pandemi covid-19 program pendidikan parenting TK ABA 26 Malang yaitu: menyediakan wadah konsultasi orang tua secara offline dan online, seminar pendidikan parenting melalui aplikasi zoom meeting dan live streaming youtube bersama narasumber ahli, pelibatan orang tua di rumah pada puncak tema. Tahapan program pendidikan parenting bersama narasumber yaitu: tahap persiapan, pelaksanaan dan evaluasi.